Enhancing feedlot cattle health: the roles of animal handling and feed additives in reducing stress and disease - Bourek, Jared Robert (My University, 2025)
The health of feedlot cattle is dependent on reducing stress and exposure to disease. Stockmen and veterinarians work together to improve health and disease outcomes in feedlot cattle through biosecurity and improving immunocompetence. Stress for cattle throughout the supply chain can come from many causes such as weather, transportation, maternal separation, digestive disruption, and many more. These stressors can result in an increase in morbidity, antimicrobial use, and subsequently mortality of cattle in feeding operations. With increased consumer pressures for reduced antimicrobial usage in red meat production, there is an increased need to evaluate these stressors to improve outcomes without the use of antimicrobials. Reducing the stress of cattle and increasing disease control directly improves cattle health, performance, and carcass characteristics while indirectly decreasing the need for antibiotics to prevent, control, or treat bacterial diseases of cattle during the finishing phase of the beef supply chain. Therefore, the objectives of these three studies were to address two specific stressors routinely observed during the feedlot phase of cattle production: 1) stress due to human-animal interactions during initial processing which could lead to increased bovine respiratory disease complex in feeder cattle and 2) stress from digestive upset that could result in liver abscesses in feeder cattle which are observed at slaughter. The first objective of this research was to evaluate the effect of handling intensity at the time of initial processing on the immune system of feedlot cattle. The second objective of this research was to evaluate the effects of antimicrobial alternatives on performance and prevalence of liver abscesses at slaughter. The results of this research indicate that aggressive handling causes negative physiological stress responses in newly received beef cattle. Secondly, this research indicates tylosin continues to be an effective fed antimicrobial for the reduction in liver abscesses. Alternative feed additives such as decoquinate may have a positive effect on the reduction of liver abscess prevalence, and feed additives such as Yucca schidigera extract may improve performance at the end of the finishing period. Decreasing stress from the first day to the final day of the feeding period leads to improved health and welfare of fed cattle.
Keywords: Animal welfare; Beef; Feedlot; Feed additives; Liver abscesses; Low stress cattle handling